Disekcija aorte - Klemen, Luka (Medicinski razgledi, 2008)
Aortic dissection is a relatively rare but life-threatening disease, characterized by a formation of a tear in the aortic wall. Any part of aorta can be affected, most commonly ascending aorta. Early diagnosis and treatment are crucial for the survival of patients, as early mortality of untreated aortic dissection is the highest over the first 48 hours. In patients with aortic pain and characteristic risk factors aortic dissection must be suspected on. The most important diagnostic methods for confirmation of aorticdissection are computed tomographic angiography, magnetic resonance imaging and echocardiography. Selection of imaging modality depends on its availability in emergency situations and patients hemodynamic instability. Thetreatment is surgical, interventional by percutaneous stenting or medical and selection of the mode of treatment depends on dissection type. Urgent surgical therapy is indicated in proximal dissection, which involves ascendingaorta. Distal dissection is generally treated medically or by percutaneous interventions. Patients require long-term follow-up, blood pressure monitoring and treatment, treatment of risk factors and recognition of complications.
Keywords: Aortic Aneurysm; Aortna anevrizma; Aneurysm, Dissecting; Anevrizma disekantna; Diagnosis; ožilje; Surgery; aorta; anevrizma; kirurško zdravljenje